Pelatihan Softskill Terhadap Kinerja Anggota Komunitas Mahasiswa Di Universitas Andi Djemma - Risna Angraeni; Dian Dian; Gita Anis (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
This study aims to analyze the effect of soft skills training on the performance of student community members at Andi Djemma University. This research employed a quantitative approach. Data were collected through questionnaires, observations, and interviews. The sample consisted of 50 respondents selected using purposive sampling. Data were analyzed using SPSS, including validity testing, reliability testing, classical assumption tests, simple linear regression analysis, the coefficient of determination (R²), and the t-test. The results indicated that all research instruments were valid and reliable. The simple linear regression analysis produced the equation Y = 1.124 + 0.974X. The t-test showed that soft skills training had a positive and significant effect on the performance of student community members, with a calculated t-value of 18.978, which was greater than the t-table value of 1.677, and a significance value of 0.000 < 0.05. Furthermore, the coefficient of determination (R²) was 0.882, indicating that 88.2% of the variation in the performance of student community members could be explained by soft skills training, while the remaining 11.8% was influenced by other factors outside the scope of this study. Therefore, soft skills training has a positive and significant effect on the performance of student community members at Andi Djemma University.